2017
DOI: 10.1063/1.4968893
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-rays from non-blazar AGN

Abstract: Abstract. Non-blazar Active Galactic Nuclei (AGN) have emerged as a new γ-ray emitting source class on the extragalactic sky and started to deepen our understanding of the physical processes and the nature of AGN in general. The detection of Narrow Line Seyfert 1 galaxies in the Fermi-LAT energy regime, for example, offers important information for our understanding of jet formation and radio-loudness. Radio galaxies, on the other hand, have become particularly interesting at high (HE) and very high (VHE) gamm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 121 publications
(143 reference statements)
0
8
0
Order By: Relevance
“…With reference to other reviews, there are many contributions by D'Ammando et al (including also some papers where NLS1s were only a section of a broader review on relativistic jets, [89,90,[140][141][142][143][144]), Ermash and Komberg [145] (general review on physical and observational properties), Boller (on history of X-ray detections [146]), and Paliya (on gamma-ray NLS1s [91]). More general reviews including sections dedicated to NLS1s were written by Rieger (gamma rays from non-blazar AGN, [147]) and Hada (high-angular resolution radio observations, [148]).…”
Section: General Reviewsmentioning
confidence: 99%
“…With reference to other reviews, there are many contributions by D'Ammando et al (including also some papers where NLS1s were only a section of a broader review on relativistic jets, [89,90,[140][141][142][143][144]), Ermash and Komberg [145] (general review on physical and observational properties), Boller (on history of X-ray detections [146]), and Paliya (on gamma-ray NLS1s [91]). More general reviews including sections dedicated to NLS1s were written by Rieger (gamma rays from non-blazar AGN, [147]) and Hada (high-angular resolution radio observations, [148]).…”
Section: General Reviewsmentioning
confidence: 99%
“…According to the unified model of active galactic nuclei (AGN) (Urry & Padovani 1995), radio galaxies are radioloud AGN that have jets beamed at large inclination angles with respect to the observer's line of sight, and are therefore sometimes termed misaligned blazars. Unlike blazars, therefore, the non-thermal radiation emitted by radio galaxies is only modestly beamed (Rieger 2017). Thus radio galaxies are very interesting targets because any detected γ-ray signal from these AGN is not dominated by the highly beamed jet emission, meaning it might be possible to disentangle jet and core emission or even to detect other potential sources of γ-ray emission.…”
Section: Introductionmentioning
confidence: 99%
“…• Centaurus A is the nearest radio galaxy in our sample (4 Mpc), and is comparable in both size and luminosity to the Milky Way. This galaxy does not show significant evidence of variability at energies above a couple of GeV [77,78].…”
Section: Gamma-ray Observations Of Nearby Radio Galaxiesmentioning
confidence: 79%
“…In this study, we focus on those radio galaxies that have been observed at TeV energies by ground-based gamma-ray telescopes (for a review of gamma-ray emission from non-blazar active galaxies, see Ref. [77]). In particular, we will consider the following list of radio galaxies (see also Table 1):…”
Section: Gamma-ray Observations Of Nearby Radio Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation